2022
DOI: 10.1111/jfd.13603
|View full text |Cite
|
Sign up to set email alerts
|

The first detection of betanodavirus reassortant genotype (RGNNV/SJNNV) isolated from gilthead sea bream (Sparus aurata) in the Turkish coastlines: The importance of screening and monitoring studies for identifying the source of the infection

Abstract: Viral nervous necrosis (VNN), caused by betanodaviruses belonging to the Nodaviridae family, poses a significant threat to aquaculture production, sustainability and development (Costa & Thompson, 2016;Thiéry et al., 2011;Toffan et al., 2017). It has been reported that 177 marine species are susceptible to betanodaviruses, and epizootic outbreaks have been reported in 62 marine species (Bandín & Souto, 2020). The most commonly affected species are the European sea bass (ESB), Asian sea bass, groupers, Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…In ongoing studies, NNV has been detected frequently in sea bass and the RGNNV genotype was identified (Kalaycı et al 2016;Kaplan and Karaoğlu 2021). The RGNNV/SJNNV genotype was also isolated from asymptomatic sea bream only in the Aegean Sea (Kaplan, Pekmez, Cagirgan, et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ongoing studies, NNV has been detected frequently in sea bass and the RGNNV genotype was identified (Kalaycı et al 2016;Kaplan and Karaoğlu 2021). The RGNNV/SJNNV genotype was also isolated from asymptomatic sea bream only in the Aegean Sea (Kaplan, Pekmez, Cagirgan, et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than being species-specific, genotypes require a water temperature at which they develop optimally (Costa and Thompson 2016;Mori et al 2005). Because of the segmented nature of the virus, the formation of reassortant strains has thus far been identified in the SJNNV and RGNNV genotypes, and RGNNV/ SJNNV or SJNNV/RGNNV reassortants have been reported many times in sea bass, sea bream and sole (Bitchava et al 2019;He and Teng 2015;Kaplan, Pekmez, Cagirgan, et al 2022;Toffan et al 2017;Volpe et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2022; Kaplan et al. 2022). In contrast, our results indicate that approximately half of the NNV‐positive individuals caught in Galician coastal waters were RGNNV/SJNNV reassortants (55%), and the other half were the SJNNV type (45%).…”
Section: Discussionmentioning
confidence: 99%
“…20 Conversely, RGNNV/SJNNV reassortant strains (Table 1) are widespread and have been isolated from farmed European sea bass, gilthead seabream, Senegalese sole (Solea senegalensis) and common sole (Solea solea) or even wild Mediterranean horse mackerel (Trachurus mediterraneus). 14,[16][17][18][19]21 Beyond its incidence in South Europe, RGNNV/SJNNV strains have been recently identified in gilthead seabream from Tunisia and Turkey rounding the Mediterranean coast, 22,23 as well as in farmed hybrid groupers (Epinephelus fuscoguttatus  Epinephelus lanceolatus) in Malasya (Figure 2). 15 The rapid spread of these reassortant strains underlines the urgent necessity of new preventive measures to control the spread of the virus.…”
Section: Nodavirusmentioning
confidence: 99%